Social communication relation of Madurese people in Max Weber rationality perspective - Budiyanti, Syamsu; Siahaan, Hotman M.; Nugroho, Kris (Jurnal Studi Komunikasi, 2020)
Obedience has become an ethnic identity for Madurese, expressed in the communicative expression ‘Bhuppa’-Bhâbbu’-Ghuru-Rato.’ Thus, the meaning of hierarchical obedience has been structured firmly into daily communication routines and behaviour as a form of self-development. The pattern of patron-client communication is a strong stimulant in the tradition of obedience that forms hegemonic power through patron-client-dominating authority. Interestingly, in Madurese society, such a relationship can actually be classified as exploitative-mutualistic. The study of rationality perspective on the meaning of communication and obedience relations shows that not all Madurese actions follow rational rules in Weber’s perspective. Indeed, there has been a reconstruction of the meaning of obedience in Madurese so that the rationality of needs becomes a justification for irrational actions and the relatively long-standing patron-client communication bond in Madurese culture. The phenomenological approach was considered most suitable for this research because it could reveal the natural meaning of Madurese specific obedience behaviour through explanation of phenomena and causes.